Brief legal analysis of the evolution of the constitutional right to education and freedom of education in Chile - González Tugas, Juan Andrés (Derecho Público Iberoamericano, 2012)
This article describes briefly and concisely the legal and constitutional evo lution of academic freedom and the right to education in Chile. The pa per is divided in seven parts: 1. Education in the indian period. 2. The education under the first Chilean constitutions. 3. The education andaca demic freedom in the Constitutions of 1828 and 1833. 4. The right to education and freedom of education in 1925 Constitution. 5. The right to education and freedom of education in 1980 Constitution. 6. The legislative development of both rights. 7. The search for balance. Finally, the article provides some conclusions about the scope and content of these rights in the Constitution.